Distorting crack-front geometry for enhanced toughness by manipulating bioinspired heterogeneity - Kaijin Wu; Zhaoqiang Song; Mengqi Liu; Zewen Wang; Si-Ming Chen; Shu-Hong Yu; Linghui He; Yong Ni (Nature Communications)
Abstract Control of crack propagation is crucial to make tougher heterogeneous materials. As a crack interacts with material heterogeneities, its front distorts and adopts complex tortuous configurations. While the behavior of smooth cracks with straight fronts in homogeneous materials is well understood, the toughening by rough cracks with tortuous fronts in heterogeneous materials remains unsolved. Here we highlight a distorted crack-front geometric toughening mechanism by manipulating bioinspired anisotropic heterogeneities of microstructural orientations and component properties. We reveal theoretically and demonstrate experimentally that the local mixed-mode I + II + III fracture triggered by local anisotropic heterogeneities lead to a helical crack front in a representative heterogeneous system with bioinspired twisted plywood structures under remote mode I loading. An anomalous nonlinear law of both the enhanced fracture resistance and the helical crack-front length versus the microstructural orientation is revealed, in contrast to the linear toughening law ignoring the hidden 3D topography within crack fronts. An optimization design protocol towards toughness amplification is developed by parametrically manipulating anisotropic heterogeneities to helically distort crack front. Our findings not only provide physical insights into the origin of biological heterogeneities modulated tortuous crack fronts but also offer a benchmark solution for enhancing toughness by parametrically engineering spatial heterogeneities.